The Effectiveness of Physical Education on the Mental Health of Grade VI Students at Sukasari Public Elementary School - Rd. Satriyaning Jagad Martadikusumah; Yudha M Saputra; Muhammad Nur Alif (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
Based on observations during the pre-research conducted by researchers on Wednesday, January 31, 2024 at Sukasari State Elementary School, not a few grade VI students complained about their worries about the results of the report card, worried that they could not meet the standard grades desired by parents. In addition, they are also worried about the national exam which will determine their graduation. Based on this, the researcher assumes that grade VI students are very vulnerable to mental health disorders. This study has tested the effectiveness of physical education on mental health in grade VI elementary school students. This study uses a mental health level measurement instrument based on the concept of mental health developed by Keyes and Lopes, mental health consists of two dimensions, namely psychological wellbeing and social wellbeing. In the results of spss calculations using descriptive statistical tests, normality tests, one sempel t tests. From this study it can be concluded that physical education is effective on the mental health of grade VI elementary school students at Sukasari State Elementary School. Because the results of the significance value (2 tailed) 0.00 <0.05 Hı is accepted. The results of this study determine that physical education variables have a significant effect on mental health.